Vitamin B2 (Riboflavin): Practical Clinical Insights for Nutritionists, Diabetes Specialists, and Pediatric Care - Khowisah, Fatemah Sami; Soad Mansour Ahmed Abbas; Khuloud Abdurhman Alamri; Wejdan Saleh Maniah; Abdulrahman Abdullah Dobaie; Abdullah Mohammed Al Amer; Aimn Mohammed Abdu Alsadi; Bandar Jahaz Alahmadi; Reem Fahad Aldosri; Abdulelah Awadh Alsuhaymi; et al. (Saudi Journal of Medicine and Public Health, 2025)
<span style="font-size: 11pt; font-family: ’Times New Roman’, serif; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Background: <span style="font-size: 11pt; font-family: ’Times New Roman’, serif; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Riboflavin (vitamin B2) is a water-soluble micronutrient essential for energy metabolism and redox reactions. While deficiency is rare in diverse diets, certain populations—pregnant women, infants, older adults, vegetarians, and individuals with malabsorption—remain at risk. <span style="font-size: 11pt; font-family: ’Times New Roman’, serif; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Aim: <span style="font-size: 11pt; font-family: ’Times New Roman’, serif; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">To provide a comprehensive clinical overview of riboflavin, including its physiological roles, pharmacokinetics, therapeutic applications, and safety considerations for healthcare professionals. <span style="font-size: 11pt; font-family: ’Times New Roman’, serif; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Methods: <span style="font-size: 11pt; font-family: ’Times New Roman’, serif; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">This review synthesizes evidence from regulatory guidelines, clinical studies, and nutritional recommendations to outline riboflavin’s mechanisms, indications, administration strategies, and monitoring approaches. <span style="font-size: 11pt; font-family: ’Times New Roman’, serif; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Results:<span style="font-size: 11pt; font-family: ’Times New Roman’, serif; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Riboflavin functions as a precursor for FAD and FMN, supporting oxidative phosphorylation and amino acid metabolism. FDA-approved use includes ophthalmic riboflavin 5’-phosphate for corneal ectasia and keratoconus. Off-label applications encompass migraine prophylaxis (400 mg/day), neonatal phototherapy support, and adjunctive therapy in antiretroviral-induced lactic acidosis. Recommended dietary allowances range from 0.3 mg/day in infants to 1.6 mg/day in lactating women, while therapeutic doses may reach 400 mg. Riboflavin demonstrates excellent safety, with minimal toxicity and rare hypersensitivity reactions. Functional assessment via erythrocyte glutathione reductase activity coefficient (EGRAC) remains the preferred monitoring method. <span style="font-size: 11pt; font-family: ’Times New Roman’, serif; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Conclusion: <span style="font-size: 11pt; font-family: ’Times New Roman’, serif; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Riboflavin is indispensable for metabolic integrity and exhibits a favorable safety profile. Its clinical utility spans preventive nutrition and targeted therapy, emphasizing the need for individualized assessment in high-risk groups.